On the power and size properties of cointegration tests in the light of high-frequency stylized facts - Christopher Krauss; Klaus Herrmann (Journal of Risk and Financial Management, 2017)
This paper establishes a selection of stylized facts for high-frequency cointegrated processes, based on one-minute-binned transaction data. A methodology is introduced to simulate cointegrated stock pairs, following none, some or all of these stylized facts. AR(1)-GARCH(1,1) and MR(3)-STAR(1)-GARCH(1,1) processes contaminated with reversible and non-reversible jumps are used to model the cointegration relationship. In a Monte Carlo simulation, the power and size properties of ten cointegration tests are assessed. We find that in high-frequency settings typical for stock price data, power is still acceptable, with the exception of strong or very frequent non-reversible jumps. Phillips-Perron and PGFF tests perform best.
Keywords: 650; cointegration testing; high-frequency; stylized facts; conditional heteroskedasticity; smooth transition autoregressive models